The efficacy and safety of endoscopic ultrasound-guided ablation of pancreatic cysts with alcohol and paclitaxel: a systematic review. Issue 1 (January 2019) - Attila, Tan; Adsay, Volkan; Faigel, Douglas O.
Abstract : Endoscopic ultrasound (EUS)-guided pancreatic cyst ablation with alcohol lavage or paclitaxel-based regimens are investigative modalities. To evaluate the safety and efficacy of EUS-guided pancreatic cyst ablation with alcohol lavage or paclitaxel-based regimens. A systematic review of computerized bibliographic databases was carried out for studies of EUS-guided pancreatic cyst ablation with alcohol lavage or paclitaxel-based regimens from January 1980 to February 2018. EUS-guided cyst ablation-related outcomes (cyst resolution) and complications. Data were extracted from six studies ( N =207 patients) for EUS-guided cyst ablation with alcohol lavage and eight studies ( N =347 patients) for EUS-guided cyst ablation with paclitaxel-based regimens. The pooled proportion of patients with complete cyst resolution was 68/207 (32.8%) for EUS-guided cyst ablation with alcohol lavage and 221/347 (63.6%) for EUS-guided cyst ablation with paclitaxel. Postablation adverse events with EUS-guided ablation with alcohol lavage were 44/207 (21.7%), and those with EUS-guided ablation with paclitaxel-based regimens were 52/347 (15%). Limitations of this study are because of the variability in study design and regimens tested, paucity of randomized trials, and differences in pancreatic cyst types receiving treatment. EUS-guided cyst ablation appears to be effective and safe. The effect on pancreatic cancer incidence is unknown; EUS-guided pancreatic cyst ablation modalities require further improvement and validation to determine their role in the treatment of patients with pancreatic cystic lesions.